Meningkatkan Kolaborasi Peserta Didik Melalui Model Problem Based Learning Fase C Kelas V SDN 047165 Simpang Nagara - Fransiska Aroniati Br Ginting (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research is classroom action research which aims to determine the effect of applying the problem based learning (PBL) model on improving students' collaboration skills on the material The Holy Spirit Strengthens the Lives of the Apostles and living together inspired by the Holy Spirit in class V Phase C SDN 047165 Simpang Nagara in the odd semester of the 2024/2025 academic year with a total of 8 students consisting of 3 men and 5 women. The method used is Classroom Action Research (PTK) with a problem base learning model which is carried out in two cycles. The research results showed that the implementation of PBL significantly improved collaboration skills and student learning outcomes, with the percentage of collaboration skills reaching 76% in cycle 1 and increasing again to 91% in cycle II. Thus, it can be concluded that the application of the Problem Based Learning model can improve students' collaboration skills on the material "The Holy Spirit Strengthens the Lives of the Apostles and living together inspired by the Holy Spirit" and the material "Involving in church life".